Mapping SPBE Challenges in Indonesia: Systematic Review by Architecture Domain - Virdha Rahma Aulia; Iqbal Ramadhani Mukhlis; Rafika Rahmawati; Tri Luhur Indayanti Sugata; Prasasti Karunia Farista Ananto; Tri Puspa Rinjeni; Nambi Sembilu (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2025)
Growing disparities in digital governance readiness across Indonesia highlight the urgency of strengthening the nation's Electronic-Based Government System (SPBE). This study conducts a systematic literature review of 34 recent studies to identify key factors that influence SPBE implementation across six architecture domains: Business (Organizational) Architecture, Data Architecture, Application Architecture, Infrastructure Architecture, Security Architecture, and Service Architecture. Drawing on the PRISMA methodology, the review uncovers recurring obstacles such as governance misalignment, fragmented system development, infrastructure limitations, inadequate data management, weak cybersecurity, and inconsistent service delivery. While these challenges inform the analysis, the proposed conceptual framework reframes each domain as a positive construct—suggesting that stronger performance in these areas contributes to greater SPBE implementation success. This framework provides policymakers with a structured lens to guide targeted digital transformation efforts. The study emphasizes the importance of policy coherence, inter-agency collaboration, human resource capacity, and integrated digital ecosystems, and invites future empirical research to validate and refine the framework through quantitative testing and in-depth case studies, particularly focusing on governance and people-centered factors.